Interleukin-34 promotes tumorigenic signals for colon cancer cells - Eleonora Franzè; Irene Marafini; Edoardo Troncone; Silvia Salvatori; Giovanni Monteleone (Cell Death Discovery, 2021)
Abstract Colorectal carcinoma (CRC) is one of the most common forms of malignancy in the Western world. Accumulating evidence indicates that colon carcinogenesis is tightly controlled by tumour-associated immune cells and stromal cells, which can either stimulate or suppress CRC cell growth and survival, mainly via the production of cytokines. Interleukin-34 (IL-34), a cytokine known to regulate mainly monocyte/macrophage survival and function, is highly produced within the CRC microenvironment by several cell types, including cancer cells, tumour-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs), and regulates the pro-tumoural functions of such cells. In this article, we summarize the available data supporting the multiple effects of IL-34 in human CRC.